MeRIP-Seq initially revealed the role of m6A modification in Chinese sacbrood virus-infected Apis cerana larvae - Liu, Yuming; Bai, Hua; Qiu, Huitong; Fei, Dongliang; Ma, Mingxiao (Frontiers in Microbiology, 2025)
Chinese sacbrood virus (CSBV) is highly lethal to honeybee larvae (especially the larva of Apis cerana) and causes considerable losses to beekeeping industry. N6-methyladenine (m6A) modification of mRNA is a predominant post-transcriptional modification in eukaryotes and plays a role in viral infection. However, the role of m6A modification in CSBV infection remains unclear. Herein, we performed high-throughput sequencing for m6A-seq in CSBV-infected and non-infected larvae to investigate host transcriptome-wide m6A modifications and identify m6A-modified genes. A total of 671 variant peaks were identified. Combined analysis of m6A modification and mRNA expression revealed that a significant correlation between mRNA methylation modifications and expression levels observed for 668 Genes. It was proved that CSBV infection can cause important m6A modification changes in host. We examined the effects of CSBV infection on expression of two methylation regulatory genes by qPCR. At the same time, we verified the effect of two methylation regulatory genes on CSBV replication using RNAi technology. This study demonstrated for the first time that CSBV infection can cause m6A modification changes in A. cerana larvae, and comprehensively analyzed the m6A modification pattern of its mRNA, and CSBV infection significantly promoted the expression of AcMETTL3 (Ac represents A. cerana, p = 0.007), but had no effect on the expression of AcMETTL14. It was further confirmed that AcMETTL3 had a significant negative regulatory effect on CSBV replication (p = 0.0432). These results lay a foundation for further exploration of the role of m6A modification in CSBV infection.